We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
68
1
avatar

How do I solve this function question?

 

 

 Mar 8, 2019
 #1
avatar+101387 
+1

(f - g) (x)  =   f(x) - g(x)  = [3x -1 ] - [5x]  = -2x - 1

 

(f * g)(x)  = f(x) *g(x)  =  [ 3x -  1] * [ 5x ]  =  15x^2  - 5x

 

(f + g)(3)  = [ 3(3) - 1 + 5(3) ] = [ 9 - 1 + 15]  = 8 + 15  =  23

 

 

 

cool cool cool

 Mar 8, 2019

13 Online Users

avatar